Three Scandinavian Countries in the Baltic Sea: A Critical Study of the Blue Economy Programmes - Sofiar, Adityarachman; Nugrahani, Henny Saptatia Drajati (UI Scholars Hub, 2024)
ABSTRACT. This paper examines the current state of the Blue Economy in the Baltic Sea region, with a focus on sustainable development in the Scandinavian countries. The paper begins by providing an overview of the economic, social, and environmental impacts. The paper identifies key challenges facing the industry in the Scandinavian countries, including the need for better planning and management, the preservation of natural and cultural heritage, and the protection of the marine environment. This research aims to explain the urgency of Blue Economy activities impact in the Baltic Sea, Specifically the impact on the environment and communities in Scandinavian Countries. To analyze the implementation of the blue economy in Scandinavian countries based on the EU Blue Economy. Using intergovernmental theory to explain the urgency and to explain the multi-level interaction between Scandinavian countries to achieve common goals. To understand complex social phenomenon researcher used qualitative research method that involves collecting and analyzing non-numerical data. In conclusion, the paper argues that sustainable blue economy in the Scandinavian countries bordering the Baltic Sea can bring significant benefits to both the marine industry and the wider community, but only if it is managed in a responsibly and sustainably manner. The paper concludes by calling for greater collaboration between stakeholders to ensure that the blue economy in the region is developed in a way that is both sustainable and inclusive, and that respects the natural and cultural heritage of the region.